NOVEL DUA IBU KARYA ARSWENDO ATMOWILOTO : KAJIAN ANTROPOLOGI SASTRA, NILAI PENDIDIKAN KARAKTER, DAN RELEVANSINYA SEBAGAI BAHAN PENGAJARAN SASTRA DI SMA - Bayu Romadi; Suyitno Suyitno; Edy Suryanto (Universitas Sebelas Maret, 2018)
Data collection techniques used in this study are documentation and in-depth interviews with informants. Data validity uses data triangulation and theory triangulation. Analysis techniques using interactive models. The main data of this research was obtained from the novel Dua Ibu by Arswendo Atmowiloto with a thickness of 300 pages. The novel is studied with a literary anthropological approach. Based on this approach, it was found that: (1) the complexity of ideas which included human relations with nature, with others, and the nature of human life; (2) the complexity of the activities that exist in Javanese society in the Dua Ibu novel; (3) the complexity of cultural results in the form of cultural results in the form of language, forms of knowledge, forms of technology, and forms of eye search; (4) the value of character education contained in the Dua Ibu novel; and (5) its relevance as literary learning in high school. The cultural life described by the author is dominated by Javanese cultural customs, namely Solo. Analysis techniques using interactive models.Conclusions from this study indicate that elements of mythology, philosophy, and Javanese culture can be used as a reference to educators, especially in Central Java for the basis of an approach to strengthen the value of the character of students and character that is in accordance with Javanese culture.